Answer: 4x+2(2x−5)−(3−5x) = 8x-10-3+5x
Step-by-step explanation: We need to find the equivalent expression to 4x+2(2x−5)−(3−5x).
Using distributive property as follows :
a(b+c) = ab+ac
4x+2(2x−5)−(3−5x) = 4x+4x-10-3+5x
= 8x-10-3+5x
Option (e)
Hence, the correct option is (e) "8x-10-3+5x"
The correct answer is 192
All you need to do is divide .88 by 6.8.
.88/6.8= 0.129 (round upt to .13 cents)
I hope this helps!
Answer:
64 cubic metres
Step-by-step explanation:
The triangular pyramid volume formula resembles the volume formula for any other pyramid or cone:
V = A * H / 3
where:
A is the area of the pyramid's base
H is the height from the base to the point
In other words: the volume of a triangular pyramid is one-third of the product of the base area and the pyramid's height.
8 x 6 / 2 to find area of base = 24
x 8 = 192
192 / 3 = 64
Hope this makes sense. If you would like, I can l1nk to a very useful website, or I can explain it further.
- profparis